Predictive Factors of the Burnout Syndrome Occurrence in the Healthcare Workers During the COVID-19 Pandemic - Grigorescu, Simona; Cazan, Ana-Maria; Rogozea, Liliana; Grigorescu, Dan Ovidiu (Frontiers in Medicine, 2022)
The COVID-19 pandemic is probably the most critical epidemiological situation that human civilization has faced in the last few decades. In this context, of all the professional categories involved in the management of patients with COVID-19 are the most likely to develop burnout syndrome. The main objective of this study is to identify and analyse specific predictive factors of the occurrence and development of the burnout syndrome in the healthcare workers involved in the diagnosis and treatment of patients with COVID-19. The study was conducted on a sample of 959 participants, medical personnel from all the public medical entities in Romania. A cross-sectional design was used. Three predictors of the burnout syndrome were identified: Work conditions, Fear of the consequences (including death) determined by the COVID-19 and Need for emotional support. Meaning of work had a moderating role. The results could be used to design specific interventions to reduce the occurrence of the burnout syndrome in healthcare workers, the implementation of a strategy to motivate employees by highlighting and recognizing the high significance of the work of those in the frontline of the fight against COVID-19.